International accounting : a user perspective - Saudagaran, Shahrokh M., 1956- (Cincinnati, Ohio : South-Western College, 2001)
This book is about: Financial reporting in the global area; Harmonizing financial reporting standards globally; Accounting for currency exchange rate changes; Selected financial reporting and disclosure issues in the global context; Using corporate financial reports across borders; Financial reporting in emerging capital markets; and Managerial issues in international accounting.
Keywords: Accounting; Comparative accounting; International business enterprises -- Accounting; Comparative accounting